Digital Transformation in Accounting: Cloud-Based AIS, Management Support, and Financial Information Quality in Retail - Michael, Michael; Ariani, Yovita; Widjaja, William (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This research departs from the low adoption of cloud-based accounting information systems in the Indonesian retail industry due to the lack of support from top management, even though this technology has proven to enhance the effectiveness of financial information. This study analyzes the influence of Cloud-based Accounting Information Systems (AIS) and top management support on the effectiveness of AIS and its impact on the quality and usefulness of financial information in Indonesian retail companies. Using a quantitative approach with a survey method, data was collected from 153 retail employees in Jakarta through questionnaires. The analysis was carried out using SEM-PLS with SMARTPLS software. The results showed that cloud-based AIS and top management support positively affect AIS effectiveness. Furthermore, AIS effectiveness improves the quality of financial information, which impacts the usefulness of financial information in decision-making. Theoretically, this study emphasizes the role of cloud technology and leadership in the effectiveness of accounting systems. As a practical implication, retail companies are advised to adopt cloud technology and strengthen management support to improve operational efficiency and financial transparency.